The relation between work, health and living conditions: negativity and positivity in nursing work at a teaching hospital (Revista Latino-Americana de Enfermagem, 2006)
This article results from a research carried out among nursing professionals at the Hospital das Clínicas da Universidade Federal de Uberlândia (MG), located in Uberlândia (MG), Brazil, and aimed to examine the relations between these professionals' work, health and living conditions. Data were collected through semistructured interviews and observations in the work environment. The results indicate the common occurrence of physical and mental health problems, mainly resulting from stress and exhaustion provoked by work conditions, which cause interferences in their living conditions. Paradoxically, the results show that these workers do not realize their health treatments systematically. The analysis of their work, in combination with the gender issue and the specific nature of nursing work, contributed to a better understanding of this professional group's work, living and health conditions.